Analysis and Implementation of High-Performance DC-DC Step-Up Converter for Multilevel Boost Structure - Premkumar, M.; Kumar, C.; Sowmya, R. (Frontiers in Energy Research, 2019)
The conventional DC-DC converters such as SEPIC, boost converter, etc. produces large voltage ripples in multilevel converter systems. For that reason, in this paper, a new DC-DC converter topology is proposed, and the performance is analyzed. Since the proposed converter delivers high conversion efficiency, it can be selected for multilevel boost DC-DC converters. The adverse effects such as inductor resistance and inductor size of the conventional converters are overcome by the proposed converter. The output voltage ripples are reduced in the proposed converter, i.e., the spikes in the converter output voltage are almost zero. The theoretical analysis is presented in this paper, which speaks about the advantage of the proposed converter. The converter operation is analyzed and discussed in continuous conduction mode (CCM). The voltage gain of the proposed converter is higher than the conventional boost converter. To validate the performance of the proposed converter, an experimental prototype is fabricated and tested in the laboratory. The performance of the converter is compared with the conventional boost and SEPIC converter. The experimental result confirms the theoretical analysis. The proposed converter can be extended by connecting more number of voltage multiplier (VM) cells to get the desired multilevel output voltage.